The Role of Marketing Communications in Management of “Enjoy Semarang” Section in Tribun Jateng Website - Arif Nurochman; Drs. Tandiyo Pradekso, M.Sc (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
With the development of technology, the public are increasingly choosing online media as the first reference when need any information. Every year the number of Internet users in Indonesia is always increase, reported by the WeAreSocial, number of active Internet users in Indonesia in 2016 amounted to 88.1 million. This makes online marketing opportunities in the future is very large and open wide. Tribun Jateng is one of mass media that converge to online media. We, as the team of the research study are working with the Tribun Jateng to manage one of its sections that focus on travel, is Enjoy Semarang. This sections very potential as the reference person reading the news and advertising medium, but because it is still new, it takes strategy and promotion to introduce this travel sections to the wider community. As a marketing communications of the research study are working with the Tribun Jateng, i conducted a strategy to raise awareness of the new channels through the off air events and also quiz on instagram and seek revenue through advertisements advertorials and social media advertising.